Migrants' choice of remittance channel: Do general payment habits play a role? - Anneke Kosse; Robert Vermeulen (European Central Bank (ECB), 2014)
This paper investigates the determinants in migrants' choice of payment channel when transferring money to relatives abroad. We surveyed 1,680 migrants in the Netherlands, identifying five remittance channels: bank services, money transfer operator (MTO) services, in-cash transfers via informal intermediaries, ATM cash withdrawals abroad and carrying cash when travelling back home. To the best of our knowledge, we are the first to present evidence of the role played by general payment habits: migrants who regularly use internet banking for other purposes are more likely to use bank services for remittances as well. However, we also demonstrate that other important drivers exist in determining the choice of payment channels, such as personal characteristics and country-specific factors, (perceived) costs, ease of use and the availability of remittance options. Based on our findings, we suggest that financial education, cost reduction and new (mobile) remittance solutions may serve a valuable role.
Keywords: F24; E42; C25; 330; payment instruments; qualitative choice models; remittances